2022
DOI: 10.6018/analesps.463101
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence and adult attachment: effects on problematic smartphone usage

Abstract: Smartphone usage can become problematic when individuals have difficulties in emotional regulation. To clarify risk factors for problematic smartphone usage, the study had three objectives: To analyze the effect of emotional intelligence and attachment dimensions on smartphone usage; to evaluate differences by types and styles of attachment in problematic smartphone usage; to explore the roles of sex and age. For this purpose, the Smartphone Dependency and Addiction Scale, the Wong & Law Emotional Intellig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…The importance of building a positive and secure attachment in childhood appears crucial for a positive image of the self and others in adulthood, in turn influencing the way in which we perceive both the offline and the online world (López et al, 2022).…”
Section: Classroom Performance Improvedmentioning
confidence: 99%
“…The importance of building a positive and secure attachment in childhood appears crucial for a positive image of the self and others in adulthood, in turn influencing the way in which we perceive both the offline and the online world (López et al, 2022).…”
Section: Classroom Performance Improvedmentioning
confidence: 99%
“…They can increase employees’ workload and burnout, which may easily lead to a conscious reduction in their work engagement and even to high turnover behaviors [ 34 , 35 ]. Research on adolescents has confirmed that smartphone addiction is closely related to individual families and interpersonal conflicts, which is an important factor that is not conducive to youth growth [ 36 , 37 ]. Smartphone addiction is more pronounced when individuals feel unkindness or aggression in the environment [ 38 ].…”
Section: Theoretical Basis and Research Hypothesesmentioning
confidence: 99%
“…En cuanto al uso problemático del teléfono móvil Aranda et al, (2022) se encontraron altos niveles de dependencia en mujeres que en hombres. Los hombres utilizan el móvil para: juegos, videos, escuchar música.…”
Section: Introductionunclassified